The Influence Self Confidence and Peer Social Support towards Optimism In Vocational High School X In Gresik - Jihan Sabila Ishmah; Idha Rahayuningsih; Ima Fitri Sholichah (Universitas Muhammadiyah Banjarmasin, 2023)
The study was intended to know if there was an influence between self-confidence and peer support for optimism in vocational high school X. The study uses a quantitative approach with a sample on this study as many as 109. The sampling technique used is saturated sampling technique. Data gathering methods by questionnaire. Researchers use a selfonfidence scale, scale of peer support and a modified optimism scale.The study states for a variable self-confidence on future optimism using a hypothetical test with a simple regression test with results that indicate a significant value of 0,000 < 0.05, which means that the hypothesis was received has been influenced by the positive (x1) students of vocational high school X with an effective and conservative contribution of 21.1% as affected by other variables outside the study, While for the social support of peers on optimism using a hypothetical test with nonlinear regression with a quadratic model that shows the value of a magnitude of magnitude is relative < 0.05, which means that hypotheses are received there is an influence of peer social support (y) to optimism with an effective 98.8%.